2019
DOI: 10.3390/molecules24142533
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Hepatoprotective Effects of Croton hypoleucus Extract in an Induced-Necrosis Model in Rats

Abstract: The aim of this study was to evaluate the antioxidant and hepatoprotective activity of Croton hypoleucus (EC). The present work reports the first pharmacological, toxicological, and antioxidant studies of EC extract on liver injury. Liver necrosis was induced by thioacetamide (TAA). Five groups were established: Croton Extract (EC), thioacetamide (TAA), Croton extract with thioacetamide (EC + TAA), vitamin E with thioacetamide (VE + TAA) and the positive control and vehicle (CT). For EC and EC + TAA, Wistar ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 66 publications
(83 reference statements)
0
7
0
Order By: Relevance
“…A single dose of TAA could produce centrilobular hepatic necrosis whereas chronic administration led to cirrhosis 11 . Several researchers reported that TAA has been an effective agent to induce liver fibrosis in experimental animals 12–17 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A single dose of TAA could produce centrilobular hepatic necrosis whereas chronic administration led to cirrhosis 11 . Several researchers reported that TAA has been an effective agent to induce liver fibrosis in experimental animals 12–17 …”
Section: Introductionmentioning
confidence: 99%
“…11 Several researchers reported that TAA has been an effective agent to induce liver fibrosis in experimental animals. [12][13][14][15][16][17] The numbers of medicinal/therapeutic plants were characterized and proved to be effective in hepatoprotective action. Some of them include, Sappan wood (Caesalpinia sappan L.), Ginger (Zingiber officinale), Java tea (Orthosiphon stamineus), Cucumis ficifolius, and Chinese chastetree (Vitex negundo).…”
mentioning
confidence: 99%
“…Other studies using TAA reported similar results [10,29]. Studies using resveratrol as an antioxidant, but in different models, also reported identical results [30]. As in other studies using flavonoids [17] and vitamin E [27], the administration of resveratrol and ε-viniferin reduced the activity of SOD compared to TAA-treated rats, achieving values similar to the controls, possibly in an attempt to adjust for the liver damage caused by the presence of the xenobiotic (Figure 3A).…”
Section: Discussionmentioning
confidence: 56%
“…Ischemia‐reperfusion injury is another cause of flap necrosis as ROS accumulate during reperfusion, leading to oxidative stress and cell damage (Chen et al, 2018; Zhao et al, 2019). SOD, an antioxidant enzyme, acts as a first line of defense against oxidative damage and neutralizes superoxide radicals to hydrogen peroxide (H 2 O 2 ) and oxygen (Urrutia‐Hernández et al, 2019; L. Zhang et al, 2016). Other proteins, such as HO1 and eNOS, also exert antioxidant effects (Sun et al, 2018).…”
Section: Discussionmentioning
confidence: 99%